Comunicação, recepção e consumo - construção de sentidos na arena do popular: a berlinda do Círio de Nazaré como suporte midiático - Junqueira, Antonio Hélio (2009)
This research aims to describe the communication process dynamics and its connections with symbolic and material consumption, under the reception studies perspective having as its media support the berlinda – a movable reliquary for the main religious icon - of the Círio de Nazaré, in Belém, Pará, Brazil. The research developed was based on the reception analysis of a communication project created by the flower producers of Pará state, and it was materialized in the substitution of traditional yellow and white flowers, imported annually from Brazil’s southeast region, by local tropical products, aiming to give a new signification and valorization to their goods. The field research was carried through October 2008 during the religious and profane events course that constitutes the Círio de Nazaré, and was made feasible by an ensemble of qualitative research practices and instruments that aligned methodological perspectives inspired in ethnographical techniques applied to research in Communication and principles and procedures of the Discourse Analysis. In the Círio de Nazaré social-cultural context and adopting the mediation analysis perspective, especially of the popular in a culture, of the religiousness, and of the different individual social status, it was possible to indicate and discuss the social dynamics of construction of meaning and the its hegemonic legitimization, emphasizing the connections between consumption and the production of identities. And, this way, search success guaranty for the producer’s objectives: the tropical flowers insertion in the daily life of the consumers.